Pendampingan Aparat Pemerintahan Kampung dalam Penyusunan Standar Pelayanan Minimal di Kampung Puay Distrik Sentani Timur Kabupaten Jayapura - Hiskia C.M. Sapioper; Dorthea Renyaan; Ibrahim K. Kendi; Jeanne J. A. Hokoyoku; Fedeli A. Itaar (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Village Minimum Service Standards (SPM) are provisions regarding the type and quality of basic services that must be received by every citizen as a form of fulfilling the basic rights of village communities. These provisions are clearly regulated in Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 2 of 2017, which serves as the basis for village governments in providing public services in a measurable and quality manner. This study aims to increase the understanding and awareness of village officials regarding the importance of public services in accordance with government-set standards. In addition, this study also focuses on assisting village officials in the process of preparing SPM documents in Puay Village, East Sentani District, Jayapura Regency. The implementation methods include lectures, question and answer sessions, group discussions, and mentoring activities carried out in several stages. These stages include identifying ongoing service problems, implementing training on SPM principles and indicators, and providing technical assistance in preparing village minimum service standards. The results of the activities indicate that village officials are able to understand and implement services according to established standards. This ability contributes to increasing the effectiveness and efficiency of services to the community, thereby significantly improving the quality of village governance.